2016
DOI: 10.3389/fpls.2015.01227
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of an Apocynum venetum DEAD-Box Helicase Gene (AvDH1) in Cotton Confers Salinity Tolerance and Increases Yield in a Saline Field

Abstract: Soil salinity is a major environmental stress limiting plant growth and productivity. We have reported previously the isolation of an Apocynum venetum DEAD-box helicase 1 (AvDH1) that is expressed in response to salt exposure. Here, we report that the overexpression of AvDH1 driven by a constitutive cauliflower mosaic virus-35S promoter in cotton plants confers salinity tolerance. Southern and Northern blotting analyses showed that the AvDH1 gene was integrated into the cotton genome and expressed. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…GWAS analyses of BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant, which was consistent with previous reports [40,50], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found that the number of repeated QTLs associated with BNPP was low under different salt conditions, implying a complex regulatory mechanism for BNPP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GWAS analyses of BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant, which was consistent with previous reports [40,50], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found that the number of repeated QTLs associated with BNPP was low under different salt conditions, implying a complex regulatory mechanism for BNPP.…”
Section: Discussionsupporting
confidence: 93%
“…Several reports have suggested that lint yield can be improved by altering the expression of salt-tolerance genes in cotton. For example, overexpressing AvDH1 in cotton can decrease membrane ion leakage, and increase the activity of superoxide dismutase, leading to salinity tolerance and increased yield [50]. Overexpression of SNAC1, which belongs to the stress-related NAC superfamily of transcription factors, could improve drought and salt tolerance by enhancing root development and reducing transpiration rate [57].…”
Section: Discussionmentioning
confidence: 99%
“…GWAS analysis on BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant which was consistent with previous reports [46,52], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found the overlapped QTLs associated with BNPP was few under different salt conditions, implying a complex regulatory mechanism for BNPP production.…”
Section: Discussionsupporting
confidence: 93%
“…Several reports have suggested that the lint yield can be improved by altering the expression of salttolerant genes in cotton. For example, overexpressing AvDH1 can decrease membrane ion leakage, along with increased activity of superoxide dismutase and lead to salinity tolerance and increasing yield in cotton [52]. Overexpression SNAC1, which belongs to the stress-related NAC superfamily of transcription factors, could improve drought and salt tolerance by enhancing root development and reducing transpiration rate in transgenic cotton [56].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that lint yield can be improved by altering the expression of salttolerance genes in cotton. For example, overexpressing AvDH1 in cotton can decrease membrane ion leakage, and increase the activity of superoxide dismutase, leading to salinity tolerance and increased yield [50]. Overexpression of SNAC1, which belongs to the stress-related NAC superfamily of transcription factors, could improve drought and salt tolerance by enhancing root development and reducing transpiration rate [57].…”
Section: Discussionmentioning
confidence: 99%